Exergetic and integrated exergoeconomic assessments of a hybrid solar-biomass organic Rankine cycle cogeneration plant. (1st July 2020) - Oyekale, Joseph; Petrollese, Mario; Heberle, Florian; Brüggemann, Dieter; Cau, Giorgio
Abstract: This study is aimed at investigating optimization potentials in a conceptual hybrid solar-biomass organic Rankine cycle (ORC) cogeneration plant, through component-based exergy and exergoeconomic analyses. The ORC is rated at 629 kWe, and it is related to a real and operational plant. Exergy balance is established in each system component, from where irreversibility rate in the respective components is obtained. Thus, exergy-based rational efficiency and efficiency defects are computed for each system component. Also, economic performance is assessed at component level, for the entire system, using conventional specific exergy costing (SPECO) approach. The energy quality level of each thermodynamic state is also integrated into SPECO formulations, providing a different way of obtaining unit exergy cost for each stream. This is termed here as integrated exergoeconomic approach. Exergy destruction cost rate, exergoeconomic factor and relative cost difference are used as criteria for exergoeconomic performance evaluation. Furthermore, the level of recoverability of exergy destruction in each of the system components is assessed, in order to identify notable improvement potentials. The evaluation of optimization potentials considers intrinsic irreversibilities in the respective components, which are imposed by the assumptions of systemic and economic constraints, and thus cannot be eliminated. Results showed that system exergetic efficiency amounts to about 11%. Also, cost of producing electricity was obtained as 10.5 c€/kWh and 12.1 c€/kWh, respectively for conventional and integrated exergoeconomic approach. Furthermore, cost of producing warm water was obtained to be lower by about 56% in integrated exergoeconomic approach, relative to the conventional approach. For the whole system, adopting integrated exergoeconomic approach led to reduced loss of investment costs by about 1.5 percent points, relative to the conventional approach.